2017
DOI: 10.1021/acscatal.7b03123
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Growth of MoS2 Nanosheets within a Mesoporous Silica Shell and Its Effects on Defect Sites and Catalyst Stability for H2S Decomposition

Abstract: Molybdenum disulfide (MoS2) is a two-dimensional transition-metal dichalcogenide that can form layered nanosheets with catalytically active sites present at edge or defect sites. The density of such active sites can be further tuned by modifying the length, layer number, strain, and surface defects of the sheets. Herein, a synthetic approach has been developed to encapsulate nanoscale MoS2 nanosheets inside a mesoporous silica shell. Small molybdenum­(IV) oxide (MoO2) cores were synthesized and coated with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 44 publications
2
49
0
Order By: Relevance
“…The remarkable catalytic performance of S−Mo 2 C/M−ZrO 2 catalyst was because of its curved ultrasmall monolayer MoS 2 structure, which is proved by Raman, XPS and TEM characterizations. It has been reported that ultrasmall monolayer MoS 2 with good dispersion can increase the density of the intrinsic active sites, such as edge sites, which is corresponding with above XPS and Raman results . At the same time, curved MoS 2 nanosheets can provide more defect sites on basal plane of MoS 2 .…”
Section: Discussionsupporting
confidence: 56%
“…The remarkable catalytic performance of S−Mo 2 C/M−ZrO 2 catalyst was because of its curved ultrasmall monolayer MoS 2 structure, which is proved by Raman, XPS and TEM characterizations. It has been reported that ultrasmall monolayer MoS 2 with good dispersion can increase the density of the intrinsic active sites, such as edge sites, which is corresponding with above XPS and Raman results . At the same time, curved MoS 2 nanosheets can provide more defect sites on basal plane of MoS 2 .…”
Section: Discussionsupporting
confidence: 56%
“…In this case, a single core template is chemically transformed to multiple catalyst particles while interior space was also created during such a process. A recent illustration of this core transformation was the synthesis of MoS 2 @ m SiO 2 structure ( Figure a,b) . In that work, spherical cores of MoO 2 were prepared first via hydrothermal synthesis with water–ethanol mixture as a cosolvent, ammonium heptamolybdate as a precursor and PVP as a capping agent.…”
Section: Catalytic Functionalization Of Hollow Materialsmentioning
confidence: 99%
“…The XRD patterns of CoS 2 ‐MoS 2 /C‐600 shows three sets of diffraction peaks that can be assigned to unreacted MoO 2 , MoS 2 (PDF#37‐1492), and CoS 2 (PDF#41‐1471), which are quite different from that of CoO‐MoO 2 /C‐600 (Figure S3 d in the Supporting Information). It can be concluded that the formed MoS 2 and CoS 2 phases originate from the MoO 2 core and CoO particles encapsulated in the carbon shell . The diffraction peaks of CoS 2 ‐MoS 2 /C‐700 also indicate the presence of MoS 2 and CoS 2 phases.…”
Section: Resultsmentioning
confidence: 92%